1996
DOI: 10.1021/om960412+
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Studies of Methylzirconocene Phosphide Complexes

Abstract: The reaction of Cp2ZrMe(PHR) with benzophenone, cyclohexanone, acetone, benzaldehyde, and benzophenone results in the insertion of the organic substrate into the Zr−P bond. In this way, the complexes Cp2ZrMe(OCPh2PH(C6H2-2,4,6-t-Bu3)) (3), Cp2ZrMe(OC6H10PH(C6H2-2,4,6-t-Bu3)) (4), Cp2ZrMe(OCMe2PHR) (R = (C6H2-2,4,6-t-Bu3) (5), R = (C6H2-2,4,6-Me3) (8), and Cp2ZrMe(NC(Ph)PH(C6H2-2,4,6-t-Bu3)) (6) were prepared. The species Cp2ZrMe(PH(C6H2-2,4,6-Me3)) (7) was also formed in the reaction of Cp2ZrMe2 with H2P(C6H2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
1
30
1
1
Order By: Relevance
“…In a similar study, the methyl complex [ZrCp 2 Me 2 ] was reacted with PH 2 Mes [45]. The stoichiometric reaction in refluxing toluene led to the formation of the phosphanyl phosphinidene complex 37 in ca.…”
Section: Scheme 19mentioning
confidence: 99%
“…In a similar study, the methyl complex [ZrCp 2 Me 2 ] was reacted with PH 2 Mes [45]. The stoichiometric reaction in refluxing toluene led to the formation of the phosphanyl phosphinidene complex 37 in ca.…”
Section: Scheme 19mentioning
confidence: 99%
“…[15] The 31 P chemical shifts of 3a-3c are similar to the values of the hitherto only known neutral zirconium phosphinidene complexes C (δ = 325.5, 303.0 ppm; see Figure 1). [4,16] The 1 H, 31 P, and 13 C NMR spectra of the products clearly indicate that there is only one configurational isomer present in solution even at low (-75°C) and high temperatures (+85°C). The composition of the novel complexes were confirmed by mass spectrometry and correct elemental analyses.…”
Section: Synthesis and Structures Of 1a-1cmentioning
confidence: 96%
“…[34,39,40] The analogous insertion of phenylacetylene afforded 18, [41] and further substitution with phenylacetylide anion gave 19. [42] We showed that ketones, aldehydes, and nitriles also insert into the ZrÀP bonds of [Cp 2 ZrMe(PHMes*)] (Mes* 2,4,6-tBu 3 C 6 H 2 ) to give products of the type F (R Ph; R' Ph, H) and G. [11] In a similar Di-and triphosphanato complexes also exhibit facile ZrÀP acidolysis and insertion reactions. For example, hydrolysis of [Cp 2 Zr{(PPh) 2 }] gave the diphosphanes (PHR) 2 .…”
Section: P à H Bond Activationmentioning
confidence: 99%
“…[11] Recently, Hey-Hawkins et al extended PÀH bond activation to monocyclopentadienyl Zr complexes. [79] Treating LiPHtBu with [{CpZrCl 3 } n ] results in a redox reaction in which Zr is partially reduced and the phosphanido group is oxidized to (PHtBu) 2 .…”
mentioning
confidence: 99%